2003
DOI: 10.1046/j.1365-2842.2003.01198.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma treatment increased shear bond strength between heat cured acrylic resin and self‐curing acrylic resin

Abstract: Self-curing acrylic resin is generally used for the repair of a fractured denture base. However, re-fracture of the repaired denture base resin often occurs because of poor bonding strength between the base resin and self-curing repair resin. The effect of plasma treatment on the shear bond strength between heat cured acrylic resin and the self-cured acrylic was examined. It was revealed that plasma irradiation is effective in increasing the shear bond strength. Plasma irradiation does not cause environmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 5 publications
0
31
0
2
Order By: Relevance
“…Atmospheric-pressure cold plasma -a complex mixture composed of ions, energetic free radicals, electrons, atoms, and molecules generated by gas discharge-has attracted much interest in biomedicine because of its potential applicability in bacterial inactivation 13,14) , tooth whitening 15,16) , blood coagulation 17) , and cancer therapy 18) . In recent years, researchers reported that plasma could be used as an economical and effective means to modify dental materials' surfaces [19][20][21][22][23] . Previous researches confirmed that after heat-cured acrylic resin was treated with cold plasma, it increased the shear bond strength between heat-cured acrylic resin and self-curing acrylic resin 21) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atmospheric-pressure cold plasma -a complex mixture composed of ions, energetic free radicals, electrons, atoms, and molecules generated by gas discharge-has attracted much interest in biomedicine because of its potential applicability in bacterial inactivation 13,14) , tooth whitening 15,16) , blood coagulation 17) , and cancer therapy 18) . In recent years, researchers reported that plasma could be used as an economical and effective means to modify dental materials' surfaces [19][20][21][22][23] . Previous researches confirmed that after heat-cured acrylic resin was treated with cold plasma, it increased the shear bond strength between heat-cured acrylic resin and self-curing acrylic resin 21) .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researchers reported that plasma could be used as an economical and effective means to modify dental materials' surfaces [19][20][21][22][23] . Previous researches confirmed that after heat-cured acrylic resin was treated with cold plasma, it increased the shear bond strength between heat-cured acrylic resin and self-curing acrylic resin 21) . Nurhaerani et al found that CF4 plasma was useful in inhibiting Streptococcus mutans adhesion on stainless steel surface 22) .…”
Section: Introductionmentioning
confidence: 99%
“…According to the previous research, the chemical adhesive property of two unlike resins can be improved with the use of surface modiflers such as plasma treatment. 13,19,20 Nonthermal plasma is one of the new methods that claims to improve bond strength between a base and a veneering material. The chemical changes include the improvement of the surface wettability and forming a functional group such as hydroxyl brought to the surface after exposure to plasma.…”
Section: Discussionmentioning
confidence: 99%
“…9,10,12 Plasma treatment has been used to modify the surface of products in the industrial world. 13 Nonthermal plasma (NTP) treatment is made of partially ionized gas with ions, electrons, and uncharged particles such as atoms, molecules, and radicals. NTP has electrons at a hotter temperature than the heavy particles that are at room temperature which are usually in helium, argon, nitrogen, helium and air.…”
Section: 대한치과보철학회지 56권 3호 2018년 7월mentioning
confidence: 99%
“…Plasma treatment is a gentle method to change the characteristics of the topmost layer of polymers. Plasma irradiation does not cause environmental pollution and is a useful method to increase adhesive strength between heat-cured acrylic resin and self-curing acrylic resin [11]. Recent study indicated that plasma treatment appeared to increase the tensile-shear bond strength between post and composite [12].…”
mentioning
confidence: 99%